2012
DOI: 10.2527/jas.2011-4262
|View full text |Cite
|
Sign up to set email alerts
|

Expression of urea transporters is affected by dietary nitrogen restriction in goat kidney1

Abstract: Ruminants are known to be able to very effectively recycle urinary urea and reuse it as a source of N for ruminal microbes. It is presumed that urea recycling is accomplished by specialized urea transporters (UT) which are localized in the kidney. This could be especially important in times of increased N requirement, such as during growth or during reduced dietary N intake. The aim of our study was to characterize and to localize UT in the goat (capra hircus) kidney and to investigate its response to reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…It showed that the increased creatinine excretion from week 0-2 was relatively constant. It was in accordance with Starke et al (2012) that high protein feed (16%) and low protein feed (11%) resulted in relatively similar creatinine excretion. Chen et al (1995); Pathak et al (2013) reported that the comparison of creatinine daily excretion was relatively constant with the amount of body protein.…”
Section: Creatinine Excretionsupporting
confidence: 87%
“…It showed that the increased creatinine excretion from week 0-2 was relatively constant. It was in accordance with Starke et al (2012) that high protein feed (16%) and low protein feed (11%) resulted in relatively similar creatinine excretion. Chen et al (1995); Pathak et al (2013) reported that the comparison of creatinine daily excretion was relatively constant with the amount of body protein.…”
Section: Creatinine Excretionsupporting
confidence: 87%
“…The existence of specific urea transporters in the mammalian kidney of monogastric animals (namely rats) has been described by several authors (Chou and Knepper 1989;Sands et al 1987). Evidence of these specific transporters in (small) ruminants has also been demonstrated for sheep (Artagaveytia et al 2005) and goat kidney (Starke et al 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Subcellular fractionations and semi-quantification of renal AQP2 and CaR protein Crude membrane fractions from renal cortex and outer medulla were prepared as previously described by Starke et al (2012). The isolation of renal brush-border membranes (BBM) was done by using a divalent-cation precipitation method described by Wilkens et al (2009).…”
Section: Sampling and Plasma Analysesmentioning
confidence: 99%
See 2 more Smart Citations